A photovoltaic degradation evaluation method applied to bifacial modules. (February 2023) - Mannino, Gaetano; Tina, Giuseppe Marco; Cacciato, Mario; Todaro, Lorenzo; Bizzarri, Fabrizio; Canino, Andrea
Highlights: A simple method for Performance Loss Ratio estimation is applied step by step to PERC bifacial photovoltaic modules. The results of the applied method are compared with the solar simulator lab test. The PLR has been estimated by the "5-STEP method" using classical PR, temperature corrected PR and bifacial PR as metric, calculated within a narrow Irradiance range filter. Abstract: The need to replace fossil energy sources with renewable energy sources to combat global warming has prompted the growth and development of various technologies, including photovoltaics. At the same time the PV technology is evolving to enhance efficiency and durability of PV modules. Bifacial PV modules is gaining larger share of market due to the higher energy and power density at almost the same price of conventional PV modules. In recent years, as PV systems have been operating for a long time, understanding the aging phenomenon of PV modules has become increasingly important. Various types of defects are known that occur during the life of the modules, however, understanding the trend of degradation through a simple quantification of the decrease in performance over time can be a useful tool. The Performance Loss Ratio can give indications about the state of health of the system and can be used for a rough comparison on the performance reduction guaranteed by the module manufacturer and check if the warranty terms are actually respected. In the present study a simple method is used to evaluate Performance Loss Ratio (PLR) on a real PV plant equipped with bifacial PERC modules. Criticalities were highlighted within each phase of the application of the method. The numerical results of the PLR estimate of the photovoltaic modules of the system are reported, calculated on a two-year dataset starting from the date of installation. Finally, the PLR values, that have been estimated using three different metrics and linear fitting, have been compared with the measured average Power decay values associated exclusively with PV modules. The simplicity of the method allows it to be replicated to other case studies.